Ambient carbon monoxide correlates with mortality risk of hemodialysis patients: comparing results of control selection in the case-crossover designs - Hyuk Huh; Ejin Kim; Una Amelia Yoon; Mun Jeong Choi; Hyewon Lee; Soie Kwon; Clara Tammy Kim; Dong Ki Kim; Yon Su Kim; Chun Soo Lim; Jung Pyo Lee; Ho Kim; et al. (The Korean Society of Nephrology, 2022)
Background Growing evidence suggests that environmental air pollution adversely affects kidney health. To date, the association between carbon monoxide (CO) and mortality in patients with end-stage renal disease (ESRD) has not been examined. Methods Among 134,478 dialysis patients in the Korean ESRD cohort between 2001 and 2014, 8,130 deceased hemodialysis patients were enrolled, and data were analyzed using bidirectional, unidirectional, and time-stratified case-crossover design. We examined the association between short-term CO concentration and mortality in patients with ESRD. We used a two-pollutant model, adjusted for temperature as a climate factor and for nitrogen dioxide (NO2), sulfur dioxide (SO2), ozone (O3), and particulate matter less than 10 μm in diameter as air pollution variables other than CO. Results Characteristics of the study population included age (66.2 ± 12.1 years), sex (male, 59.1%; female, 40.9%), and comorbidities (diabetes, 55.6%; hypertension, 14.4%). Concentration of CO was significantly associated with all-cause mortality in the three case-crossover designs using the two-pollutant model adjusted for SO2. Patients with diabetes or age older than 75 years had a higher risk of mortality than patients without diabetes or those younger than 75 years. Conclusion Findings presented here suggest that higher CO concentration is correlated with increased all-cause mortality in hemodialysis patients, especially in older high-risk patients.